TETANUS TOXOID VACCINATION AS A PREMARITAL ADMINISTRATIVE REQUIREMENT IN ISLAMIC COMMUNITY GOVERNANCE: A MASLAHAH MURSALAH ANALYSIS AT KUA PALENGAAN, PAMEKASAN - Hidayat, Shohibul; Wusqo, Urwatul (Jurnal Al-Ijtimaiyyah, 2026)
Premarital Tetanus Toxoid (TT) vaccination serves as both a public health intervention and an instrument of Islamic community governance, raising important questions about the integration of health policy with Islamic legal principles. This study examines the implementation of TT immunization as an administrative requirement for marriage registration at the Religious Affairs Office (Kantor Urusan Agama/KUA) of Palengaan District, Pamekasan Regency, East Java, Indonesia, through the analytical lens of maslahah mursalah. A descriptive qualitative field study was employed, integrating sociological and normative approaches. Primary data were collected through semi-structured interviews with nine informants — including the Head of KUA Palengaan, KUA administrative staff, healthcare workers at the Palengaan Community Health Center (Puskesmas), and prospective brides and grooms — complemented by direct observation and institutional documentation. Secondary data were drawn from official regulations, fiqh literature, and previous scholarly studies. The findings reveal that TT immunization is predominantly perceived by the community as an administrative formality rather than a meaningful health intervention, owing to limited public health literacy and inadequate policy socialization. From the perspective of maslahah mursalah, the TT vaccination policy generates significant public benefit (maslahah), particularly in protecting human life (hifz al-nafs) and preserving progeny (hifz al-nasl) — two of the five primary objectives of Islamic law (maqasid al-shari'ah). The policy is classified at the level of hajiyyah (secondary functional welfare), constituting a preventive jurisprudential strategy (sadd al-dhara'i') against reproductive health risks for mothers and newborns. However, a gap persists between the policy's normative Islamic legal legitimacy and its practical social implementation. The study contributes to interdisciplinary scholarship on the integration of public health policy and Islamic law, and recommends enhanced community health education, improved cross-sectoral coordination between KUA and healthcare institutions, and culturally contextualized policy communication to optimize the program's effectiveness within Muslim community settings.